Distribution of air quality health benefits of medium and heavy-duty electrification policies in New York City - Brian Naess; Jonathan Buonocore; Veronica Southerland; Muskaan Khemani; Catherine Seppanen; Ananya Roy; Frederica Perera; Kaitlyn E Coomes; Rick Rykowski; Saravanan Arunachalam (Environmental Research: Health)
Increased electrification of the transportation sector promises to both decrease emissions from the largest sector source of greenhouse gases as well as improve health through better air quality. The objective of this study is to evaluate the distribution of air quality health benefits of Medium- and Heavy-Duty Electric Vehicle (MHDEV) policies in New York City (NYC), quantifying differences across neighborhoods (census tracts) and population subgroups (race, ethnicity). We ran an integrated model for a 2040 baseline/business-as-usual scenario and for two policy scenarios simulating different rates of MHDEV adoption, also for 2040. Changes in air quality (fine particulate matter (PM _2.5 ) and nitrogen dioxide (NO _2 )) and health and economic benefits were calculated for the two policy scenarios. We used a modified version of our previously developed ZIP Code-Level Air Pollution Policy Assessment tool which integrates two reduced form models: the Community Air Quality Tools and the Co-Benefits Risk Assessment Health Impacts Screening and Mapping Tool. Our air quality modeling employed a novel receptor network to capture sharp gradients due to medium- and heavy-duty vehicle (MHDV) emissions in the densely populated NYC region. We find that electrification of MHDVs would have substantial air pollution and health benefits for NYC, with full on-road electrification of MHDVs saving $2.4 billion in health costs in 2040, including the prevention of 248 deaths and 173 childhood asthma emergency departments visits. We find that NO _2 benefits contributed between 85% and 97% of the total health benefits, emphasizing its importance for on-road health studies. We find that most health benefits would occur in neighborhoods with the highest percentage of historically marginalized populations, including substantial benefits to Hispanic populations.